Scheduling and Simulating Wireless HART Systems - Zakupszki, Andras; Pichetpongsa, Nuttapon; Seceleanu, Tiberiu (EUROMICRO (IEEE Computer Society Press), 2014)
Control processes and the communication between them must be scheduled appropriately, such that the I/O data is correlated. Here, we illustrate the design and realization of a Wireless HART system development tool, meant to support design decisions in communication and processing scheduling.